(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Intrauterine contraceptive devices (IUCD) is an effective, reversible long term contraceptive method. Uterine perforation is one of the rare & most significant complication of IUCD which commonly occurs during primary insertion rather than presenting as delayed migration. This is a case of migrated IUCD into the left iliac fossa of abdomen wrapped in the omentum, diagnosed incidentally due to abdominal pain. IUCD was retrieved successfully by laparoscopic approach. So, regular follow up plays crucial role to diagnose early complication. Case report: A 18 years old girl P-1 (VD), ALC -14 months, was admitted to Gynae department of ShSMCH with a history of lower abdominal pain for 2 months & incidental diagnosis of extra-uterine IUCD. It was inserted 45th day of postpartum. After insertion she was regularly menstruating with average flow & duration. But she developed continuous dull aching abdominal pain for last two months then visited to a local doctor. USG & X-ray of abdomen revealed extra-uterine IUCD in left iliac fossa. Hence, she was referred to ShSMCH for retrieval. On examination her general condition was good & abdomen was soft but mild tenderness over the left iliac region. On laparoscopy CuT along with omentum embeded to left side of the parital wall which was removed after adhesiolysis while small amount of pus come out. Discussion: IUCD migration has a great impact on patient physical & mental health. WHO recommends surgical removal of the migrated IUCD by minimally invasive method. Follow up after insertion is crucial for early diagnosis of migration. Conclusion: All migrated IUCD must be removed as it can cause bowel & bladder perforation, fistula formation. Missing CuT- 380A can be diagnosed by USG, X-ray, CT scan. Our case was detected by USG & X-ray. Removal by laparo-hysteroscopy is best approach depending upon location. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(2): 117-119